The Influence of Gender and Education Issues on Youth Political Interest: Evidence from Metro - Nugroho, Dwi; Risvana, Audy Anzany; Solehah, Tika Amirul (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2024)
Abstract In recent decades, young people's political participation has emerged as a significant topic of political debate, given their role as agents of future social and political change. Many political actors conduct practical politics in a variety of ways to mobilize young people's choices. This research intends to explore young people's interest in political ideas that can cater to future requirements. This study used a hybrid method (quantitative and qualitative), combining survey data from 130 respondents, (samples were determined using the Lemeshow formula) and in-depth interviews with 12 Muslim and 3 non-Muslim. This study focuses on the perspectives of vulnerable young students aged 17 to 20 as first-time voters in Metro-Lampung. This study reveal that education and gender issues had a positive and significant influence on political interest of young people more than economic issues which many politicians campaign for public. It has been qualitatively proven that youths, both Muslims and non-Muslims, have a proclivity for gender and educational issues in making political choices. These findings imply that political ideas that are in line with the needs of young people and are a response to problems developing in society can influence youth political interest.